Assessment of TGF-β3 on production of aggrecan by human articular chondrocytes in pellet culture system - Saeed Zamani; Batool Hashemibeni; Ebrahim Esfandiari; Azadeh Kabiri; Hossein Rabbani; Roshanak Abutorabi (Advanced Biomedical Research, 2014)
Background: The Autologous Chondrocytes Transplantation (ACT) method is being studied for repair of cartilage diseases. As the chondrocytes dedifferentiated during monolayer culture, three-dimensional cultures are suggested to redifferentiate them. The aim of this study was investigation of the effect of TGF-β3 growth factor on chondrocytes in pellet culture system. Materials and Methods: The chondrocytes were isolated from three human articular cartilages by enzymatic digestion. The cells of the second passage were transferred to pellet culture system. We determined the chondrogenic medium with TGF-β3 as the experimental group and without it as the control group. After 2 weeks, the aggrecan production was investigated using histological and immunohistochemical (IHC) methods. Results: The presence of glycosaminoglycans was proved through Toluiden blue staining. Comparison of IHC results using MATLAB software showed that aggrecan in the experimental group was significantly higher than in the control group (P ≤ 0.05). Conclusion: The presence of TGF-β3 in the chondrogenic medium could lead to the production of more aggrecan in chondrocytes cultivated in pellet culture system.